IMPLEMENTATION OF THE E-BUDDY SIDOARJO APPLICATION IN DIGITAL-BASED OFFICIAL LETTER MANAGEMENT IN KEBOGUYANG VILLAGE, JABON DISTRICT - Syamsudyan, Muhammad; Choiriyah, Ilmi Usrotin (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the implementation of the E-Buddy application in digital official letter management in Keboguyang Village, Jabon District, with a focus on its effectiveness, encountered obstacles, and the role of village officials. Method: A qualitative descriptive approach was employed, with data collected through interviews, observations, and document analysis. The research applied George C. Edward III’s policy implementation theory—covering communication, resources, disposition, and bureaucratic structure—and utilized Miles & Huberman’s model for data analysis, including data reduction, presentation, and conclusion drawing. Results: Findings indicate that the E-Buddy application has positively influenced administrative efficiency by accelerating processes, enhancing organization, and promoting transparency. Training programs significantly improved officials’ technical understanding, while the application facilitated smoother and more structured administrative workflows. Novelty: A unique contribution of this study lies in the participatory knowledge dissemination observed, where village officials proactively shared insights from technical guidance with peers, independent of formal training. This grassroots initiative highlights an overlooked dimension of community-driven capacity building in digital governance, offering valuable insights for broader e-government implementation in rural contexts.